Eli Harpo's adventure to the afterlife : a novel - Schlich, Eric, 1988- (The Overlook Press, 2024)
"Award-winning author Eric Schlich's Eli Harpo's Adventure to the Afterlife is an accessible and big-hearted novel that explores belief and forgiveness as a boy grapples with his faith and sexuality on a rollicking family road trip to Bible World. When Eli Harpo was four, he underwent emergency open-heart surgery, flatlined on the operating table, and for a brief time, went to heaven and met Jesus. Or at least that's what his father, a loving but devout Baptist minister, has raised him to believe. Nine years later, Eli isn't so sure. His rounds with his father to evangelize at hospices and sell his father's self-published book, Heaven or Bust! , feel inauthentic and strange, especially now that he's started having sex dreams about Jesus. Between that and his mother's terminal breast cancer diagnosis, Eli feels further from heaven than ever. But when the famous televangelist Charlie Gideon shows up at the Harpos' doorstep with a proposal to create a new attraction based on Eli's trip to the afterlife at his Bible-themed park, Eli isn't able to say no. As the Harpos head off on a rollicking road trip from Kentucky to Bible World in Orlando, Eli is left to grapple with not just his faith and his sexuality, but also his own parents' messy humanity and what happens when a family held together by mythmaking starts coming apart at the seams. Hilarious and moving, Eli Harpo's Adventure to the Afterlife is a kind-hearted story about self-discovery and the search for truth, wherever it takes you." --